Sales essentials : the tools you need at every stage to close more deals and crush your quota - Salman, Rana (McGraw Hill's business essentials., 2023)
"With so much focus put into making a sale, many professionals find they need help improving the crucial points that come before and after the sale. In Sales Essentials, you'll find the comprehensive, up-to-date information you need to improve your skills at every point of the sales process before, during, and after to ensure you've mastered all the tools you need to further your career"--